2015
DOI: 10.3109/14756366.2014.971781
|View full text |Cite
|
Sign up to set email alerts
|

Novel thiosemicarbazides induced apoptosis in human MCF-7 breast cancer cells via JNK signaling

Abstract: In this study, novel thiosemicarbazides and 1,3,4-oxadiazoles were synthesized and evaluated for their anticancer effects on human MCF-7 breast cancer cell lines. Among the synthesized derivatives studied, compound 2-(3-(4-chlorophenyl)-3-hydroxybutanoyl)-N-phenylhydrazinecarbothioamide 4c showed the highest cytotoxicity against MCF-7 breast cancer cells as it reduced cell viability to approximately 15% compared to approximately 25% in normal breast epithelial cells. Therefore, we focused on 4c for further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Also, JNK functions to directly phosphorylate Bcl-2 (B-cell CLL/Lymphoma-2) to enable co-localizing and collaborating with Bcl-2 to mediate prolonged cell survival [39]. Increased expressions of JNK and Bcl-2 in cancer cells were not desirable, and as such cancer cell proliferation could be inhibited if this pathway was modulated [40,41]. Accordingly, both extracts significantly downregulated JNK expression with FxRF exhibiting a significantly higher downregulating effect than CME treatment (p < 0.05).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Also, JNK functions to directly phosphorylate Bcl-2 (B-cell CLL/Lymphoma-2) to enable co-localizing and collaborating with Bcl-2 to mediate prolonged cell survival [39]. Increased expressions of JNK and Bcl-2 in cancer cells were not desirable, and as such cancer cell proliferation could be inhibited if this pathway was modulated [40,41]. Accordingly, both extracts significantly downregulated JNK expression with FxRF exhibiting a significantly higher downregulating effect than CME treatment (p < 0.05).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We next aimed to explore the underlying mechanism by which KRT19 regulates cancer reprogramming. Although KRT19 regulates EGR1/PTEN/AKT, β-catenin/NUMB/NOTCH, and HER2/ERK/SP1 cascades [ 29 , 46 , 47 ], we focused on the AKT, GSK3β, ERK, Src, and JNK signaling pathway in this study, as these signaling pathways are crucially involved in cancer progression [ 52 , 53 , 54 , 55 , 56 ]. The WB analysis demonstrated that the phosphorylation of p-GSK3β (Tyr216) and p-Src levels were increased significantly upon the knockdown or overexpression of KRT19 in MDA-MB231 or KU-CSLC cells, while the expression of p-AKT, p-GSK3β (Ser9), p-ERK, and p-JNK was unchanged ( Figure 6 C,D), which is suggested that KRT19 could regulate the cancer stem cell reprogramming by partially modulating the phosphorylation of GSK3β (Tyr216) and Src in breast cancer or cancer stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, thiosemicarbazides are one of the most promising biologically active compounds which can be used in cancer treatment (Arora et al , 2014 ; Mohsen et al , 1981 ). These derivatives have been effectively used against a number of carcinoma cell lines (Perković et al , 2012 ; Bhata et al , 2008 ; Malki et al , 2014 ; Zhang et al , 2011 ). It has been found that thiosemicarbazide derivatives demonstrated cytotoxic and antiproliferative activity against HeLa, HepG2, MDA-MB-231 and HT-29 cell lines (Mavrova et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%